The Influence of Physical Environment and Customer’s Satisfaction towards Customer’s Loyalty - Ali Syah Putra; Eddy; Erina Alimin; Hengky Kosasih; Albert (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The purpose of this study was to determine the effect of physical environment and customer satisfaction on customer loyalty at Zen Okane Pematang Siantar. This research is a type of quantitative research. The population in this study are all consumers who make purchases at the Zen Okane Pematang Siantar, the number of which is unknown. The sampling technique using the Lemeshow sampling technique obtained as many as 96 research samples. The method of collecting data in this research is literature study and questionnaires. Methods of data analysis using descriptive analysis and simple linear regression analysis. The results showed that the value tcount (4.858) > ttable (1.985) with a significance of 0.000 < 0.05 so it can be concluded that there is an influence between Physical Environment on the Customer Loyalty. The value of tcount (4.748) > tTable (1.985) with a significance of 0.000 < 0.05 so it can be concluded that there is an influence between Customer Satisfaction on the Customer Loyalty. Simultaneous Testing Results (F-Test), the value of Fcount (27.409) > FTable (3.09) with a significant of 0.00 < 0.05 so it can be concluded that H3 is accepted with the understanding that there is an influence between Physical Environment and Satisfaction on the Customer Loyalty.